Bringing Meanings: AI And Human Collaboration In Unveiling Qur’anic Synonymy and Polysemy - Albalawi, Abdulrahman Fahad (Ijaz Arabi Journal of Arabic Learning, 2025)
The rich linguistic texture of the Holy Qur’an presents unique difficulties in maintaining the integrity of meanings across languages, especially given the complex interplay of synonyms that often carry subtle distinctions. This study aims to elucidate the contextual meanings, analyse the polysemous nature of بأس (ba’s) (punishment), and investigate the semantic distinctions between the near-synonymous terms بأس (ba’s) and بطش batsha (assault) and their AI-generated and post-edited English translations of the Qur’an. Adopting the Relation by Contrast Approach to Synonyms (RC-S) by Murphy (2003), the study utilises a qualitative approach to identify the semantic layers of meanings of the selected Qur’anic synonyms. The analysis reveals that بأس (ba’s) is polysemous in the Qur’anic text, capturing diverse meanings like punishment, battle, and hardship, reflecting its complex usage in enhancing thematic and rhetorical aspects of verses, unlike its near-synonym بطش (batsha) which is more narrowly defined as "assault." While ChatGPT’s translations of بأس (ba’s) vary in accuracy, highlighting the AI’s challenge in capturing context-specific meanings, the translation of بطش (batsha) as "grasp" fails to convey the aggressive connotations of "assault," which necessitates significant refinements by human editors to align renderings more closely with the original’s military and theological contexts.